2020
DOI: 10.1074/jbc.ra119.011945
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac myosin regulatory light chain kinase modulates cardiac contractility by phosphorylating both myosin regulatory light chain and troponin I

Abstract: Heart muscle contractility and performance are controlled by posttranslational modifications of sarcomeric proteins. Although myosin regulatory light chain (RLC) phosphorylation has been extensively studied both in vitro and in vivo, the precise role of cardiac myosin light chain kinase (cMLCK), the primary kinase acting upon RLC, in the regulation of cardiomyocyte contractility remains poorly understood. In the current study, using recombinantly expressed and purified proteins, various analytical methods, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…We interpret the biosensor FRET transient as reporting TnC's global conformational change, from extended to compact, during the twitch, as based on extensive in vitro work on TnC [17,36,53,54]. During a twitch, we posit that the TnC-tethered FRET probes Clover (donor) and mRuby2 (acceptor) move closer together, consistent with the increased FRET signal observed.…”
Section: Discussionmentioning
confidence: 53%
“…We interpret the biosensor FRET transient as reporting TnC's global conformational change, from extended to compact, during the twitch, as based on extensive in vitro work on TnC [17,36,53,54]. During a twitch, we posit that the TnC-tethered FRET probes Clover (donor) and mRuby2 (acceptor) move closer together, consistent with the increased FRET signal observed.…”
Section: Discussionmentioning
confidence: 53%
“…Structural insights into the IHM and SRX are supported by functional measurements in isolated trabecular muscle, where it has been shown that cRLC phosphorylation increased the rate of force re-development after muscle release ( Sevrieva et al, 2020 and Toepfer et al, 2016b ). This result inferred that the mechanism of action of RLC phosphorylation is the increase in Huxley's N a parameter, which is consistent with a reduction of SRX and increase in DRX myosin states ( Craig et al, 1987 ; Nag et al, 2017 ; Toepfer et al, 2016b ).…”
Section: Regulation Of Myosin Srx By Protein Level Phosphorylation Amentioning
confidence: 97%
“…As cardiac MLCK contains an autoregulatory segment, it is likely to play a role similar to those of smMLCK and skMLCK. Most studies showed that MLCK is an RLC-dedicated kinase [ 95 ] until a recent study showed that human MLCK phosphorylates both RLC and troponin I (TnI) [ 96 ]. The following questions remain: (1) What are the roles of other kinases?…”
Section: The Role Of Regulatory Light Chains In Normal and Diseased Heartsmentioning
confidence: 99%